Avances sobre la identificación de originalidad en cerámicas prehispánicas 2025 - Gonzalez Espino, David (2026)
Ceramic collections in the custody of public or private entities must be cataloged and identified for their originality as part of collections that are potential for conservation and exhibition. However, to date, there is no evidence or indicators that determine the originality of a ceramic piece. The objective of the research was to perform an analysis to identify the originality of pre-Hispanic ceramics using preventive conservation reagents. The methodology was quantitative, basic, and non-experimental. Regarding the results, we have that the mean control limit (MCL) was determined at 3.56 minutes as a parameter for the originality of a ceramic piece. Regarding the mean control limits for black ceramics, they are 4.96 minutes, which determines that most are replicas. Regarding the results for orange ceramics, they are 3.34 minutes, indicating that most are originals. And regarding the results for cream-colored ceramics, we have 2.37 minutes, which determines that they are originals.